Self-Enhancement and Self-Protection Strategies in China: Cultural Expressions of a Fundamental Human Motive - Hepper, Erica G.; Sedikides, Constantine; Cai, Huajian (Journal of cross-cultural psychology, 2013)
The motive to enhance and protect positive views of the self manifests in a variety of cognitive and behavioral strategies, but its universality versus cultural specificity is debated by scholars. We sought to inform this debate by soliciting self-reports of the four principal types of self-enhancement and self-protection strategy (positivity embracement, favorable construals, self-affirming reflections, defensiveness) from a Chinese sample and comparing their structure, levels, and correlates to a Western sample. The Chinese data fit the same factor structure and were subject to the same individual differences in regulatory focus, self-esteem, and narcissism, as the Western data. Chinese participants reported lower levels of (enhancement-oriented) positivity embracement but higher levels of (protection-oriented) defensiveness than Western participants. Levels of favorable construals were also higher in the Chinese sample, with no differences in self-affirming reflections. These findings support and extend the universalist perspective on the self by demonstrating the cross-cultural structure, yet culturally sensitive manifestation, of self-enhancement motivation.